PERAN KEBIJAKAN DEVIDEN DALAM MEMODERASI RETURN ON ASSETS DAN DEB EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI PERIODE 2021 -2023 - Friyan Hidayah; Triska Dewi Pramitasari; Lita Permata Sari (Fakultas Ekonomi dan Bisnis, 2025)
Financial management has a very important role in creating company value, especially in the property and real estate sector which is known for its high asset value. This study aims to analyze the effect of Debt to Equity Ratio (DER) and Price to Book Value (PBV) on the stock price of property and real estate companies listed on the Indonesia Stock Exchange, and test the moderating role of Earning Per Share (EPS) in the relationship between the two financial ratios. The population in this study involved all property and real estate companies listed on the Indonesia Stock Exchange. Samples were taken using purposive sampling method based on certain criteria during the research period. Data analysis was carried out with a Structural Equation Modeling approach based on Partial Least Square (PLS-SEM) using SmartPLS 3. 0 software. The results of hypothesis analysis show that both Debt to Equity Ratio (DER) and Price to Book Value (PBV) have a significant positive effect on stock prices. However, Earning Per Share (EPS) is not proven to moderate the relationship between Debt to Equity Ratio and Stock price. On the other hand, Earning Per Share actually acts as a significant amplifier of the positive relationship between Price to Book Value and Stock price.